Peran Disiplin Kerja dalam Meningkatkan Kinerja Karyawan pada Klinik Larizma Husada - Agnes Elsy Wardhany Sihura; Enik Rahayu (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This article aims to analyze the role of work discipline in improving employee performance at Larizma Husada Clinic in Harjosari, Bawen District, Semarang Regency. The problem focuses on how work discipline is implemented in service activities and its implications for employee performance and the quality of services perceived by patients. To address this issue, this study is grounded in human resource management theory and employee performance theory. This research employs a qualitative approach with a descriptive qualitative design. Data were collected through in-depth interviews, direct observation, and documentation involving informants consisting of clinic management, clinic employees, as well as patients or patients’ family members. The data were analyzed qualitatively through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that employee work discipline is reflected in punctuality, compliance with standard operating procedures, job responsibility, and service ethics, which play an important role in improving work orderliness, task effectiveness, and the quality of health services. This study concludes that work discipline is not only understood as a formal obligation but also as a professional commitment and moral responsibility in providing optimal health services, thereby contributing to improved employee performance and overall clinic service quality.